Cancer Treatment Disease Application Software Technology in Medicine - Tawafak R.M.; AlFarsi G.; Malik S.I.; Eldow A.; Jabbar J.; Alsideiri A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cancer is caused by damage to the genes that control cell growth and division. however, still many applications try to Detection/diagnosis/treatment is possible using application software. By confirming cell growth and treatment by correcting the mechanism of gene damage or by stopping the blood Supplying cells or by destroying them. this study tries to answer the question: How to prove a possible disease outbreak? the literature review investigated the Analysis of requirements involved in the design and development of FBP. The method develops a simple software, divided into multi phases as an alternative to regular clinical visits. The main requirements of this application cover Concepts and terms of clinic needs match with patient disease level. The software results show the satisfaction of patients who uses the software for the early process of generating information through the User interface, to reduce any distrust or concerns. 2020 IEEE.